Developing effective sheep mineral supplementation strategies in Ireland - Hession, Daniel (2022)
Minerals perform many important functions in the body with a mineral imbalance having detrimental effects on the performance, fertility, health and profitability of livestock. Co is of particular importance in sheep with even marginal deficiencies leading to poor animal performance. Therefore, there is a need for appropriate effective and sustainable mineral supplementation strategies for grass based sheep systems. The aims of this thesis were to generate new information on the prevalence of mineral deficiencies, current supplementation practices and the response to mineral supplementation in flocks grazing pastures, thus enabling evidence based decisions on mineral nutrition of ewes and lambs.